The Influence of The Discovery Learning Model on Student Learning Outcomes on Subtema 1 Animals and Plants in My Home Environment Class IV Students at State Primary School 091254 Batu Onom - Reginantaras Ginting; Minar Trisnawati Lumabantobing; Partohap S.R. Sihombing (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of the discovery learning model learning on student learning outcomes in subtheme 1 animals and plants in the Rumahkundi environment for class IV SD Negeri 091254 Batu Onom. This type of research is quantitative research that uses experimental methods. The experimental research used in this research is pre - experimental in the form of One Group Pretest - Posttest Design . The samples for this research were 30 class IV students. The instruments used are pretest and posttest tests which have been carried out validation and reliability tests. The research results at the 0.05 level show that there is an influence of the discovery learning model on student learning outcomes in subtheme 1 animals and plants in my home environment in class IV of SD Negeri 091254 Batu Onom. It can be seen that the results of the pretest and posttest comparison have a sig value of 0.000, which means it is smaller than the value of 0.05, and t has a value of 24.650. This means that there is an influence of the Discovery Learning Learning Model on learning outcomes. Changes in student learning outcomes taught using the discovery learning model make students think more actively, understand the material presented, increase students' curiosity in searching for and finding information on their own, compared to students taught without using the discovery learning model learning.